Perancangan Aplikasi Pengolahan Citra Digital Untuk Penajaman Sisi Citra Hasil Fingerprint Menggunakan Metode Fourier Phase Only Synthesis - Siagian, Novita (CV. Graha Mitra Edukasi, 2023)
Detecting fringerprints (fingerprints) is one way to sharpen image results to make them look clearer and cannot be manipulated. In general, the attendance system used by employees is still mostly done manually. This has many weaknesses where in addition to data that can be easily imitated, the time is not clear, it also takes quite a long time. So to avoid this, an electronic system is needed. In this case the system that will be used is the fingerprint method. The development of image processing technology now provides the possibility for humans to create a system that can recognize a digital image. Various image processing applications that have been developed at this time include security systems, the world of robotics, and so on. Image processing is one type of technology to solve problems regarding image processing. In image processing, images are processed in such a way that they can be used for further applications. The fingerprint recognition system must be able to identify a person's fingerprint from a large set of fingerprint databases. This is a separate problem for the efficiency of the identification system. Therefore, various classification approaches are used based on the general characteristics that appear in fingerprints. The process begins with detecting the fringerprint result by sticking your finger on the scan machine, then the image will be detected and the image is sharpened with a value using arithmetic operations. The results of image processing are indicated by changes in the resulting image and fourier image changes. In this case the system that will be used is the fingerprint method. This fingerprint system uses the fourier phase only synthesis method.